2018
DOI: 10.1016/j.bbrc.2018.03.107
|View full text |Cite
|
Sign up to set email alerts
|

Detection and proteomic characterization of extracellular vesicles in human pancreatic juice

Abstract: Together our data show that detection and characterization of EVs directly in pancreatic juice is feasible and may prove to be a valuable source of potential biomarkers of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
3
36
0
1
Order By: Relevance
“…As carriers of disease‐associated molecules that can be found in biofluids, EVs have great potential as a noninvasive source of biomarkers for diseases such as cancer. Recently three groups (Hwang, Buzás, and Xiao) have performed comparative proteomic analysis on EVs from disease‐associated biofluids . Proteomic analysis of EVs from biofluids has been shown to decrease the background signal derived from highly abundant proteins, such as creatine in urine, resulting in greater sensitivity .…”
Section: Proteomic Profiling Of Evs In Clinical Samplesmentioning
confidence: 94%
See 2 more Smart Citations
“…As carriers of disease‐associated molecules that can be found in biofluids, EVs have great potential as a noninvasive source of biomarkers for diseases such as cancer. Recently three groups (Hwang, Buzás, and Xiao) have performed comparative proteomic analysis on EVs from disease‐associated biofluids . Proteomic analysis of EVs from biofluids has been shown to decrease the background signal derived from highly abundant proteins, such as creatine in urine, resulting in greater sensitivity .…”
Section: Proteomic Profiling Of Evs In Clinical Samplesmentioning
confidence: 94%
“…For example, a large number of EV proteins isolated from urine specimens of bladder cancer patients were not identified by proteomics perfomed on straight urine without EV isolation . In line with this, a large number of EV proteins isolated from pancreatic juice of patients with chronic pancreatitis or pancreatic cancer were not identified when proteomics was performed on pancreatic juice without EV isolation . In both cases, the number of proteins that were identified only in the EV samples were ≥40%.…”
Section: Proteomic Profiling Of Evs In Clinical Samplesmentioning
confidence: 96%
See 1 more Smart Citation
“…One such promising approach involves identification of secreted extracellular vesicles (EV) in the blood of patient to differentiate patients with PDAC from both patients who are disease-free or those with chronic pancreatitis (benign conditions). Several studies have attempted to identify EV associated protein using conventional cell lines in culture with further validation using blood samples from PDAC patients and healthy controls (4,(22)(23)(24). It is not clear whether organoid cultures can be used to discover new, clinically significant, secreted biomarkers.…”
Section: Organoids As Discovery Platform For Blood-based Biomarkers Imentioning
confidence: 99%
“…Previous studies have identified glypican‐1 (GPC1), different types of mucins, the multidrug resistance protein 1 (MDR1) and the cystic fibrosis transmembrane conductance regulator (CFTR) in these vesicles, highlighting the potential of exosomes as circulating markers of pancreatic cancer . Further, pancreatic cancer exosomes have been shown to target and modulate pre‐metastatic niche formation in the liver through macrophage migration inhibitory factor (MIF), initiating profound phenotypic changes in the liver to coordinate metastasis .…”
Section: Introductionmentioning
confidence: 99%